2002
DOI: 10.1002/cne.10186
|View full text |Cite
|
Sign up to set email alerts
|

Axonopathy, tau abnormalities, and dyskinesia, but no neurofibrillary tangles in p25‐transgenic mice

Abstract: Neurofibrillary tangles, one of the pathologic hallmarks of Alzheimer's disease (AD), are composed of abnormally polymerized tau protein. The hyperphosphorylation of tau alters its normal cellular function and is thought to promote the formation of neurofibrillary tangles. Growing evidence suggests that cyclin-dependent kinase 5 (cdk5) plays a role in tau phosphorylation, but the function of the enzyme in tangle formation remains uncertain. In AD, cdk5 is constitutively activated by p25, a highly stable, 25kD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 61 publications
4
69
1
Order By: Relevance
“…Thus, neurotoxicity induced by ␤-amyloid, ischemia, or MPTP causes aberrant Cdk5 activity through the generation and accumulation of p25 (Cruz and Tsai, 2004;Dhariwala and Rajadhyaksha, 2008). Furthermore, this truncated p25 form relocalizes Cdk5 activity with the consequent alteration of Cdk5 substrate specificity (Patrick et al, 1999;Ko et al, 2001;Bian et al, 2002). Actually, elevated Cdk5 activity accumulation of p25 and hyperphosphorylated tau have been described in brain of AD patients (Cruz and Tsai, 2004;Dhariwala and Rajadhyaksha, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, neurotoxicity induced by ␤-amyloid, ischemia, or MPTP causes aberrant Cdk5 activity through the generation and accumulation of p25 (Cruz and Tsai, 2004;Dhariwala and Rajadhyaksha, 2008). Furthermore, this truncated p25 form relocalizes Cdk5 activity with the consequent alteration of Cdk5 substrate specificity (Patrick et al, 1999;Ko et al, 2001;Bian et al, 2002). Actually, elevated Cdk5 activity accumulation of p25 and hyperphosphorylated tau have been described in brain of AD patients (Cruz and Tsai, 2004;Dhariwala and Rajadhyaksha, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the p25-Cdk5 complex was shown to be harmful to neurons, as evidenced by cytoskeleton disruption, neuritic retraction and expression of apoptotic markers (Ahlijanian et al, 2000;Bian et al, 2002;Patrick et al, 1999;Hamdane et al, 2003a). Interestingly, deregulation of Cdk5 activity by association with its activator p25 is likely to be involved in AD pathogenesis (Lee et al, 1999;Patrick et al, 1999;Patrick et al, 2001;Cruz et al, 2003;Noble et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of p25 protein have also been found in the postmortem brain tissue of AD patients (Patrick et al, 1999;Tseng et al, 2002). Although this has been debated by a number of groups (Takashima et al, 2001;Bian et al, 2002), the proteolytic cleavage of p35 to p25, which has been shown to hyperactivate Cdk5 is without doubt. Deregulation of Cdk5 activity, accompanied by the accumulation of p25 has been implicated as a causative factor in the pathogenesis of neurodegenerative diseases (Nguyen et al, 2001;Smith et al, 2006).…”
Section: Introductionmentioning
confidence: 99%